Institutionalized bailouts and fiscal policy : the consequences of soft budget constraints - Alexander Fink; Thomas Stratmann (Center for Economic Studies and ifo Institute (CESifo), 2009)
States have soft budget constraints when they can expect a bailout by the federal government in the event of a financial crisis. This gives rise to incentives for unsound state fiscal policy. We test whether states with softer budget constraints have higher debt and deficits, receive more bailouts funds, spend funds less efficiently, and are more likely to allocate funds to programs benefiting special interests. Exogenous variation in soft budget constraints across states and over time allows the identification of budget constraint softness on state fiscal policy. We take advantage of the fact that in Germany, states' political influence is exogenous because voting weights differ in the upper chamber of the German parliament. The stronger the political influence of states, the softer their budget constraints. We show that states with softer budget constraint have higher deficits and debts, and receive more bailouts funds. Further, overrepresented states are less efficient in spending public funds and are more prone to respond to rent seeking by interest groups.
Keywords: H70; H11; E62; E63; 330; Finanzpolitik; Budgetrestriktion; Rent Seeking; Haushaltsdefizit; Öffentliche Schulden; Teilstaat; Länderfinanzen; Deutschland